Advanced Practice Nursing and the Expansion of the Role of Nurses in Primary Health Care in the Americas - Luís Carlos Lopes-Júnior RN, MSc, PhD (SAGE Publishing, 2021)
Nurses have an educational background particularly suited to the growing challenges of the 21st century, characterized by an accelerated demographic transition, accompanied by a scenario of triple disease burden: 1) the unsurpassed agenda for infectious diseases; 2) the increase in deaths attributable to external causes; and 3) the predominance of chronic noncommunicable diseases. Advanced Practice Nurses (APN) already have regulations well-established in many countries such as Australia, Belgium, Canada, the USA, Finland, France, Ireland, Japan, Poland, the United Kingdom, and the Czech Republic, among others. This paper aimed to point out and to reflect on Advanced Practice Nursing and the expansion of the role of nurses in Primary Health Care (PHC) in the Americas. In the same year the Nursing Now Campaign was launched, Pan American Health Organization (PAHO) and World Health Organization (WHO) prepared the document Expanding the Role of Nurses in PHC which calls on governments and nurses from countries in the Americas to implement APN training for PHC and Nurses from Central and South America who already have specialization programs, residency, academic master's and doctoral degrees. Expansion is intended to provide greater coverage and assistance to users of the health system, take advantage of nurses' intellectual capacity, and retain good professionals in the profession. This is a crucial moment for nursing worldwide. However, it is imperative to ensure the voice and impact of nursing continues to reverberate long after the end of 2021. In this paper, a debate on the strengths and challenges for the expansion of the APN role in PHC in the Americas is discribed.